Alterations in fingerprints of polychlorinated biphenyls in benthic biota at the Portland Harbor Superfund Site (Oregon, USA) suggest metabolism. (May 2019) - Rodenburg, Lisa A.; Delistraty, Damon A.
Abstract: In order to understand the sources and fate of polychlorinated biphenyls (PCBs) in several species of benthic biota, including clams ( Corbicula fluminea), oligochaetes (Lumbriculus variegatus), and mussels (Margaritifera falcata and Anodonta nuttalliana ) at the Portland Harbor Superfund Site (PHSS), their congener fingerprints were examined. First, diagnostic ratios of congeners known to be metabolizable vs. recalcitrant in the cytochrome P450 (CYP) pathway were significantly lower in biota than in its co-located sediment, indicating metabolism may have occurred. Next, the congener patterns were analyzed using Positive Matrix Factorization (PMF). The dominant fingerprint (by mass) in benthic biota is related to Aroclor 1260 but displays differences in the fingerprint that are consistent with weathering via absorption, distribution, metabolism, and excretion (ADME). This fingerprint is similar to one isolated from PCBs in fish from Washington State, indicative of common metabolic pathways and consistent with CYP metabolism. When metabolism is taken into account, the spatial distribution of the PMF-isolated PCB fingerprints in biota matches well with those from co-located sediment samples, suggesting that the same mix of sources at one location partitions into biota and sediment. In accordance to their higher hydrophobicity, higher molecular weight (MW) PCB formulations were proportionately more abundant in biota than in sediment, although low MW PCBs (e.g., PCBs 4 and 11) do bioaccumulate in benthic organisms and should not be ignored in risk assessment efforts. Finally, fingerprinting suggests potential reasons why lab-based and field-based biota-sediment accumulation factors (BSAFs) differ substantially for bivalves. Highlights: Congener patterns of PCBs in benthic biota from the Portland Harbor Superfund Site were analyzed. Paired samples of sediment and biota showed differences in PCB fingerprints and congener ratios. These differences imply metabolism via the cytochrome P450 pathway in clams, worms, and mussels.